PERSOALAN SAMPAH DALAM TERANG PEMIKIRAN ISLAM (Sebuah Catatan Evaluatif terhadap Status Manusia sebagai Abdi Allah dan Khalifah) | THE PROBLEM OF GARBAGE IN THE LIGHT OF ISLAMIC THOUGHT (Notes on the Status of Men and Women as Servants of God and as Caliphs) - Hendrikus Maku (Institut Filsafat dan Teknologi Kreatif Ledalero, 2017)
Abstract: The problem of garbage is the issue of how human beings understand and bring alive the concept of himself or herself. Islam as a Gospel of Action has a certain perspective about human beings and the environment. Human beings, as written in some letters and hadith, are the most perfect part of God’s creation (kāmil) to whom two status are attributed, namely servant of God and Caliph. As servant of God and as Caliph, human beings are God’s chosen creation who are entrusted to take care of the universe. If so, then the problem of garbage which arises from the brutality of humans is a provocation attacking the status of human beings as the servant of God and Caliph. Keywords: Garbage, Islam, God, the servant of God, Caliph, human beings. Abstrak: Persoalan sampah adalah persoalan tentang bagaimana manusia memahami dan menghidupi konsep tentang dirinya. Islam sebagai agama amal memiliki perspektif tertentu mengenai manusia dan lingkungannya. Manusia, sebagaimana tersurat dalam beberapa surat dan hadit adalah ciptaan Allah yang paling sempurna (kāmil), padanya diatributkan status sebagai Abdi Allah dan Khalifah. Sebagai Abdi Allah dan Khalifah, manusia adalah ciptaan pilihan Allah yang dipercayakan untuk merawat alam semesta. Kalau demikian, maka persoalan sampah yang lahir dari rahim kebiadaban manusia adalah sebuah gugatan terhadap jati diri manusia sebagai Abdi Allah dan Khalifah. Kata-kata kunci: sampah, Islam, Allah, abdi Allah, Khalifah, lingkungan hidup, manusia.